Pendampingan Kelompok Tani Dalam Penerapan Mesin Perontok Padi Guna Meningkatkan Efisiensi Pascapanen Di Kabupaten Garut - Agus Saleh; Riri Damayanti Apnena; Edison Ginting; Yoddy Agung Nuhgraha; Setiyana - (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2026)
Rice farming plays a significant role in supporting food security and improving rural livelihoods in Indonesia. However, many farmers still rely on conventional threshing methods that are labor-intensive, time-consuming, and result in considerable post-harvest losses. This community service program aimed to improve the efficiency of post-harvest activities by introducing appropriate technology in the form of a rice threshing machine accompanied by technical guidance for its operation and maintenance. The program was conducted with a farmer group in Cibatu District, Garut Regency, West Java, using a participatory approach consisting of needs assessment, equipment handover, technical training, hands-on practice, and evaluation. The results demonstrated that participants successfully acquired the knowledge and practical skills required to operate and maintain the machine safely and effectively. The implementation of the rice threshing machine significantly reduced processing time, minimized grain losses, decreased labor requirements, and enhanced farmers' productivity during the post-harvest process. Furthermore, the technical guidance increased farmers' confidence in adopting appropriate agricultural technology to support sustainable farming practices. This community service activity highlights that the integration of appropriate technology and capacity-building initiatives can effectively strengthen farmers' capabilities, improve post-harvest efficiency, and contribute to increased agricultural productivity and rural community welfare.